The Internet World and its Influence on Our Mind - Usmanov Elbek Mamatkodirovich (Researchparks Publishing, 2022)
The article discusses the increasing use of the Internet among the representatives of different strata of the population of our society, including the youth, the increasing need for information and the intensification of information attacks, the positive and negative effects of the Internet on our consciousness.